Pengaruh Model Pembelajaran Direct Instruction Berbantuan Bahan Ajar Berbasis Kontekstual Terhadap Hasil Belajar IPA Terapan Siswa Kelas X SMKN 4 Mataram Tahun Ajaran 2015/2016 - Puryadi Puryadi; Satutik Rahayu; Sutrio Sutrio (Department of Physics Education, Universitas Mataram, 2018)
This study aims to determine the effect learning model of direct instruction assisted contextual based teaching materials to the students learning outcomes of applied science SMKN 4 Mataram of academic years 2015/2016 on temperature and heat matter. This type of research is an experimental study with post test design control group design. The population in this study were all students of class X SMKN 4 Mataram of academic years 2015/2016. Sampling is done by purposive sampling technique, selected of X2 culinary class as experiment class and student of class X3 culinary as control class. The teaching materials used are context based physics teaching materials to culinary students. Instruments used in the form of multiple-choice test questions that refer to students' cognitive abilities include C1 to C6 categories. The results showed that the mean values of the students' learning outcomes of the experimental class and control classes were 61.38 and 49.07, respectively, both classes were normal and homogeneously distributed. The results data were analyzed by two-party test with a significance level of 5% obtained trsesult 2.89 and ttable 2.00. If tresult > ttable. So Ho is rejected and Ha is accepted. So it can be concluded that there is the influence learning model of direct instruction that is assisted by contextual based teaching materials on the learning outcomes of students of class X SMKN 4 Mataram of academic years 2015/2016.